2022
DOI: 10.3390/nu14030679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Supplementation on Inflammatory Parameters: A Meta-Analysis of Randomized Controlled Trials

Abstract: Magnesium (Mg) may have several beneficial effects on human health outcomes. One hypothesized mechanism eliciting such effects is the action of Mg on serum inflammatory parameters. However, studies on this topic to date have several important limitations. Therefore, the present systematic review and meta-analysis aimed to summarize the current state of the art of all randomized control trials (RCTs) investigating the effects of Mg supplementation versus placebo on serum parameters of inflammation. We searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Although studies suggest that magnesium have anti-inflammatory and immunomodulatory effects, 3 , 13 , 20 , 21 to the best of our knowledge, there is only one study of the anti-edematous effect of magnesium in inflammation, and our results are in agreement with Nagai et al, 10 who showed that preventive systemic administration of magnesium (Mg 2+ 10–200 mg/L) reduced edema in experimental mycobacteria-induced arthritis. There are, however, some differences between our studies: the type of inflammation (acute vs chronic), the choice of inflammatory substances (carrageenan vs Mycobacterium butyricum ), administration of magnesium (s.c. and single administration and per os via drinking water, repeated daily for 42 days), evaluation of dose-dependent vs dose-independent effects.…”
Section: Discussionsupporting
confidence: 91%
“…Although studies suggest that magnesium have anti-inflammatory and immunomodulatory effects, 3 , 13 , 20 , 21 to the best of our knowledge, there is only one study of the anti-edematous effect of magnesium in inflammation, and our results are in agreement with Nagai et al, 10 who showed that preventive systemic administration of magnesium (Mg 2+ 10–200 mg/L) reduced edema in experimental mycobacteria-induced arthritis. There are, however, some differences between our studies: the type of inflammation (acute vs chronic), the choice of inflammatory substances (carrageenan vs Mycobacterium butyricum ), administration of magnesium (s.c. and single administration and per os via drinking water, repeated daily for 42 days), evaluation of dose-dependent vs dose-independent effects.…”
Section: Discussionsupporting
confidence: 91%
“…Another meta-analysis of RCTs indicated that magnesium supplementation reduced CRP levels among individuals with inflammation (CRP levels > 3 mg/dL) [ 35 ]. A most recent meta-analysis also showed that magnesium supplementation significantly decreased CRP [ 36 ]. A RCT among diabetic patients showed that magnesium supplementation significantly decreased IL-6 levels, which is another key inflammatory marker [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these effects, in fact, might contribute to the reduction in the ventilation-perfusion mismatch, which is one of the most important reasons for hypoxemia in COVID-19, and to the improvement of oxygenation in these patients [ 87 ]. Additionally, because of the emerging role of mastocytes in driving diffuse alveolar injury in COVID-19 [ 88 ], it should be recalled that Mg may reduce mastocyte degranulation and, subsequently, prevent the release of inflammatory, pro-thrombotic and fibrotic mediators [ 89 ].…”
Section: Discussionmentioning
confidence: 99%